Juvenile Systemic Lupus Erythematosus Presenting with Esophagitis and Severe Oral Mucositis - Schildt, Emily; Sessions, Kristen L; De Ranieri, Deirdre (Case Reports in Rheumatology, 2021)
We present a case of a previously healthy adolescent female who developed severe oral mucositis and acute esophagitis as her presenting symptoms of juvenile systemic lupus erythematosus. Mucositis involving the lips is infrequently reported in systemic lupus erythematosus, and to our knowledge, this is the first reported case of acute, non-infectious esophagitis as a presenting symptom in a pediatric systemic lupus erythematosus patient.